An assessment of prime‐boost vaccination schedules with AS03A‐adjuvanted prepandemic H5N1 vaccines: a randomized study in European adults. Issue 1 (9th March 2012) - Gillard, Paul; Caplanusi, Adrian; Knuf, Markus; Roman, François; Walravens, Karl; Moris, Philippe; Dramé, Mamadou; Schwarz, Tino F.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Gillard et al. (2012) An assessment of prime‐boost vaccination schedules with AS03A‐adjuvanted prepandemic H5N1 vaccines: a randomized study in European adults. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2012.00349.x. Background Long‐term persistence of immune response and safety of an H5N1 prepandemic influenza vaccine adjuvanted with AS03 (an α‐tocopherol oil‐in‐water emulsion‐based adjuvant system) was evaluated using various prime‐boost schedules that mimicked potential pandemic scenarios (NCT00430521). Methods Five hundred and twelve healthy adults aged 18–60 years received primary vaccination with one or two doses (0, 21 days schedule) of the A/Vietnam/1194/2004 H5N1 vaccine followed by a booster dose (A/Vietnam/1194/2004 or A/Indonesia/05/2005 strain) six or twelve months later across eight randomized groups. Immunogenicity results by hemagglutination inhibition [HI] assay, microneutralization assay, and the cell‐mediated immune response (CMI) are reported here for the four groups boosted at Month 12. Results A one‐dose‐adjuvanted primary administration followed 12 months later by a single‐adjuvanted booster dose containing a heterologous vaccine strain met or exceeded all US and European criteria for both strains. Increasing the interval between the first and second dose (from 21 days to 12 months) resulted in stronger cross‐reactive immune responses against the A/Indonesia/05/2005 strain. The HI antibody response against the two strains persisted for 6 months after the booster dose irrespective of the booster vaccine's strain. The neutralizing antibody responses and the CMI observed in the study population paralleled the HI immune response. Overall, the vaccine had a clinically acceptable safety profile. Conclusion The H5N1 vaccine in this study allowed for flexibility in the time interval between primary and booster vaccination and the use of a heterologous strain without impacting the strength of the humoral and cellular immune response to both vaccine strains.